COVID-19 VACCINE HESITANCY FOR CHILDREN IN PARENTS: A CROSS-SECTIONAL SURVEY AMONG HEALTH-CARE PROFESSIONALS IN INDIA - HIMANSHI; KADAM, KRANTI S; U UTTARWAR, PARUL (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: There is evidence of morbidity and mortality in children due to COVID-19 infection. “Vaccine Hesitant Parents (VHPs)” may act as barriers to vaccination of children and their knowledge, attitude, beliefs, and perceptions come into play. Health-care providers are cited as the most important source for vaccine information by VHPs, and provider recommendation for vaccination is crucial for improving vaccine uptake. Hence, we aim to study among Indian health-care professionals having children <18 years of age, the prevalence of parental hesitancy for pediatric COVID-19 vaccine and to assess their knowledge, attitude, beliefs, and perceptions about pediatric COVID-19 vaccine. Methods: An observational, cross-sectional study was conducted across India through a web-based questionnaire amongst health-care professionals having children less than 18 years of age by Snowball sampling technique. Descriptive statistics were used to study the demographic profile, the prevalence of vaccine hesitancy, and individual factors. Correlations between the datasets were obtained using regression analysis and significance level using the Chi-square test. Results: The prevalence of COVID-19 vaccine hesitancy for children in Indian health-care professionals is 3.3%. The most important source of information was the internet and social media. The majority of the participants knew about the vaccine and its side effects (p=0.00) and believed in the usefulness of the vaccine in preventing infection (p=0.008) and in reducing severity (p=0.009). All these factors lead to better vaccine acceptance. Conclusion: These data show that vaccine acceptance has improved over time and thus HCWs can aid in reducing vaccine hesitancy.